Do direct-democratic procedures lead to higher acceptance than political representation?: Experimental survey evidence from Germany - Towfigh, Emanuel V.; Goerg, Sebastian J.; Glöckner, Andreas; Leifeld, Philip; Llorente-Saguer, Aniol; Bade, Sophie; Kurschilgen, Carlos (Public choice, 2016)
Are direct-democratic decisions more acceptable to voters than decisions arrived at through representative procedures? We conduct an experimental online vignette study with a German sample to investigate how voters’ acceptance of a political decision depends on the process through which it is reached. For a set of different issues, we investigate how acceptance varies depending on whether the decision is the result of a direct-democratic institution, a party in a representative democracy, or an expert committee. Our results show that for important issues, direct democracy generates greater acceptance; this finding holds particularly for those voters who do not agree with a collectively chosen outcome. However, if the topic is of limited importance to the voters, acceptance does not differ between the mechanisms. Our results imply that a combination of representative democracy and direct democracy, conditional on the distribution of issue importance among the electorate, may be optimal with regard to acceptance of political decisions.